Internet Use Habits, Parental Control and Psychiatric Comorbidity in Young Subjects with Asperger Syndrome. - Coskun, Murat; Hajdini, Aydan; Alnak, Alper; Karayagmurlu, Ali (Journal of Autism & Developmental Disorders, 2020)
We aimed to investigate the characteristics of internet use in a clinical sample of 60 young subjects with Asperger Syndrome (AS) and its relationship with parental control and psychiatric comorbidity. Of the participants, 38.3% were classified as having problematic internet use (PIU). Subjects with normal internet use (NIU), compared to the subjects with PIU, had significantly higher scores on parental control scale. While there was no significant difference in terms of any comorbid diagnoses between subjects with NIU versus PIU, severity of depressive symptoms was found to predict higher scores on Young Internet Addiction Scale (YIAS). In conclusion, PIU may be common in AS and may be associated with internalizing problems, while parental control may protect against it.